2009
DOI: 10.1504/ijbra.2009.022461
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of protein phosphorylation site predictors with an independent dataset

Abstract: Protein phosphorylation plays a fundamental role in most of the cellular regulatory pathways. Experimental detection of protein phosphorylation sites is labour intensive and often limited by the availability and optimisation of enzymatic reactions. The in silico prediction of phosphorylation sites using protein's primary sequences may provide guidelines for further experimental consideration and interpretation of phosphoproteomic data. An array of such tools exists over the internet and provides the prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The independent benchmark dataset, named B in this study was collected from the article [17]. It contained 297 phospho-proteins and Table 6 shows the number of positive and negative sites in these proteins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The independent benchmark dataset, named B in this study was collected from the article [17]. It contained 297 phospho-proteins and Table 6 shows the number of positive and negative sites in these proteins.…”
Section: Resultsmentioning
confidence: 99%
“…6 and 7) with 211, 85 and 97 phosphorylated sites of serine, threonine and tyrosine respectively in the article [17] and the performance of the five existing prediction systems (PPSP [6], DISPHOS [8], KinasePhos [11], NetPhosK [10] and Scansite 2.0 [12]) were tested with these 393 annotations. But from Table 6, it can be found that more phosphorylation annotations were done by Phospho.ELM server (ver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dataset is originally from [33], where it was used to assess the performance of existing predictors. The annotations of this dataset are updated based on Release 9.0 of the Phospho.ELM database [11].…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, different protein phosphorylation site predictors have not been intensively benchmarked via some independent datasets in the literature. Sikder and Zomaya (2009) developed an independent dataset, collected from Phospho.ELM, to compare the performances of KinasePhos, NetPhosk, DISPHOS, Scansite and PPSP [21]. However, this independent dataset contained mainly mammalian proteins.…”
Section: Introductionmentioning
confidence: 99%